(untitled) (Zoo Botanica, 2025)
The Thread-Winged Lacewing, Croce filipennis Westwood, 1841 (Neuroptera: Nemopteridae), is recorded for the first time from southernmost region of Punjab, Pakistan. This finding expands the C. filipennis geographic range into South Asia’s arid and semi-arid regions. The finding emphasizes the importance of focused biodiversity surveys in Pakistan’s poorly understood ecosystems, especially in habitats that are ecologically significant but frequently disregarded. The detailed diagnostic morphological traits are presented to aid in precise identification. This finding underscores the potential for additional knowledge on Neuropteran diversity within the country.